Food Culture as a Narrative Technique and Cultural Identity in Upendra Subba-Directed Jaari - Rai, Prakash; Senehang, Dipankar (Tribhuvan University Journal, 2025)
The gastronomy, or culinary practice cover various meanings across different cultures and contexts. As food reflects culture internally, it becomes more challenging to communicate precise meanings and cultural insights through food discussions when the audience share a distinct cultural background. However, Upendra Subba’s movie Jaari portrays Limbu cultural practices and rituals, using food as a narrative tool to exhibit the Limbu culture and identity. In this regard, the paper explores gastronomy as a narrative technique and cultural commentary in Limbu socio cultural praxis to address three specific research questions: What aspects of Limbu food culture are woven into the socio-cultural fabric of the Limbu community? How does the practice of food consumption serve as a narrative device to depict Limbu culture and identity? Why does food culture, as a narrative approach, play a crucial role in shaping and expressing Limbu socio-cultural identity? In order to answer the questions, the paper has employed Mary Douglas’s concept of food as communication system and categorization and Roland Barthes’s ideas of food as social semiotics. The answers and the analysis based on the interrogation reveal that food functions as a metaphor in socio-cultural spaces, carrying multiple meanings, with its metaphoric significance potentially revealing the most authentic way of life. It argues that food not only serves as semiotic system but as a storytelling device to communicate the Indigenous aesthetics of the Limbu community and connect deep cultural meanings with people’s everyday life and actions.